2013
DOI: 10.1103/physrevlett.110.083602
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Envelope-Phase Effects in Ultrafast Strong-Field Ionization Dynamics of Multielectron Systems: Xe andCS2

Abstract: Carrier-envelope-phase- (CEP) stabilized 5 and 22 fs pulses of intense 800 nm light are used to probe the strong-field ionization dynamics of xenon and carbon disulfide. We compare ion yields obtained with and without CEP stabilization. With 8-cycle (22 fs) pulses, Xe(6+) yields are suppressed (relative to Xe(+)) by 30%-50%, depending on phase, reflecting the phase dependence of nonsequential ionization and its contribution to the formation of higher charge states. Ion yields for Xe(q+) (q = 2-4) with CEP-stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Similar studies on CO have predicted that two-color pulses can be used to control molecular orientation [4,12,13]. These theoretical predictions have been realized in experiments starting from the neutral targets H 2 [14][15][16][17][18], D 2 [13,15,[18][19][20][21][22], HD [19,23], CO [4,13,[24][25][26], DCl [27,28], and small polyatomic molecules [29][30][31][32][33][34][35][36][37]. More recently, experimental CEP control has been demonstrated directly on H + 2 [38][39][40].…”
Section: Introductionmentioning
confidence: 87%
“…Similar studies on CO have predicted that two-color pulses can be used to control molecular orientation [4,12,13]. These theoretical predictions have been realized in experiments starting from the neutral targets H 2 [14][15][16][17][18], D 2 [13,15,[18][19][20][21][22], HD [19,23], CO [4,13,[24][25][26], DCl [27,28], and small polyatomic molecules [29][30][31][32][33][34][35][36][37]. More recently, experimental CEP control has been demonstrated directly on H + 2 [38][39][40].…”
Section: Introductionmentioning
confidence: 87%
“…They found that laser-driven recollisional ionization and excitation caused a π-periodic oscillation of the ionization and fragmentation yields with CEP. Mathur et al studied the strong-field dissociative ionization dynamics of CS 2 molecules and found CEP-dependent modulations in the fragmentation yields [44]. Processes depending on the direction of the electric field have also been predicted for larger molecules (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35]). CEP effects in the deprotonation of acetylene, induced by few-cycle laser pulses, have attracted considerable interest.…”
Section: Introductionmentioning
confidence: 99%